Menganalisis Belajar Siswa Berkebutuhan Khusus Slow Learner di Sekolah Dasar Negeri Keleyan 1 - Iqbal Sauqi; Nova Estu Harsiwi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Children with special needs are children who have their own individuality in terms of types and characteristics, which distinguish them from normal children in general. Learning difficulties are more related to psychological disorders such as frustration, anxiety, adjustment barriers and emotional disorders, so learning difficulties can be related to psychological factors, especially personality, adjustment disorders and self-confidence. This study aims to determine the learning difficulties experienced by students with special needs. The method used is descriptive using qualitative data analysis so that it becomes an easy-to-understand data exposure. The selection of research subjects consisted of one classroom teacher, one GPK teacher, and one student with special needs. The results showed that there were students with special needs who were categorized as slow learners. Students experience difficulties during the learning process such as difficulty recognizing letters and numbers.